Revitalisasi Organisasi Sektor Publik - Mas Roro Lilik Ekowanti (Universitas Riau, 2009)
The public sector organization in giving services to public is not tends standardizationyet. The purpose of using the standardization of public sector organization is to raise the publicservices performance. In the term of preparing the standardization is as one of the alternative way toincrease the performance through revitalization. Public sector revitalization should be arranged bythe strategic plan according to the conception of public administration with the final result that thestrategic plan can be implemented by the bureaucracy in area. Besides, the truth in choosing theacademic study is as the guidance in arranging strategic plan with excellent services standardiza-tion. So that, the arrangement process of strategic plan considering the right external and internalvariable and also the tool’s analysis which used in the concept. By using variable and tool’s analy-sis, the excellent services can be implemented and being responsible to public.